2020
DOI: 10.1007/s00181-020-01967-4
|View full text |Cite
|
Sign up to set email alerts
|

Determining the efficiency of residential electricity consumption

Abstract: Increasing energy efficiency is a key global policy goal for climate protection. An important step toward an optimal reduction of energy consumption is the identification of energy saving potentials in different sectors and the best strategies for increasing efficiency. This paper analyzes these potentials in the household sector by estimating the degree of inefficiency in the use of electricity and its determinants. Using stochastic frontier analysis and disaggregated household data, we estimate an input requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Although the total number of publications in Germany is only 50, 48 of the articles are collaborative papers. Germany holds a leading position in renewable energy and energy development, and it collaborates with the United States and other European countries in joint research in this field (Andor et al, 2021;Heesen and Madlener, 2021). The USA and the United Kingdom, as the most productive countries, maintain cooperation with 14 countries and have the strongest partnership with China.…”
Section: Country and Regionmentioning
confidence: 99%
“…Although the total number of publications in Germany is only 50, 48 of the articles are collaborative papers. Germany holds a leading position in renewable energy and energy development, and it collaborates with the United States and other European countries in joint research in this field (Andor et al, 2021;Heesen and Madlener, 2021). The USA and the United Kingdom, as the most productive countries, maintain cooperation with 14 countries and have the strongest partnership with China.…”
Section: Country and Regionmentioning
confidence: 99%
“…Alberini et al [53] found that up to 17% of energy demanded by households in the US is consumed due to persistent inefficiencies, Andor et al [54] calculated this value on German data to be equal to up to 20% and estimate on Swiss households' data the electricity saving potential to 25% [55]. These results indicate that at least a share of household's energy poverty may be improved by increasing efficiency of household's appliances even though Orea et al [56] argue that efficiency improvements are questionable due to rebound effects.…”
Section: Costs Associated With Property Ownershipmentioning
confidence: 99%
“…The authors suggest rather policies aimed on increasing energy efficiency via incentives promoting a change of habits in the use of equipment, increasing energy literacy [57], and by offering incentives on the purchase of new, high-efficiency equipment and technologies. Andor et al [54] recommend targeting such energy policy to selected groups as obviously a nationwide appliance of replacement program would result being too expensive. In this regard, Davis et al [58] using the case of Mexican policy of subsidized replacement of household's refrigerators and air conditioners with energy-efficient models demonstrates a rebound effect that counteracts some of the savings.…”
Section: Costs Associated With Property Ownershipmentioning
confidence: 99%
“…But these are not simple rote applications. Many have new and interesting datasets (Hazarika and Paul 2020;Argüelles and Orea 2020;O'Loughlin and Wilson 2021;Andor et al 2020;Mosheim and Sickles 2021). Nearly all of the papers that appear here put forth major econometric and economic advances for these well-worn models and in a variety of subdisciplines of econometrics: nonparametric, spatial, Bayesian, index numbers, etc.…”
mentioning
confidence: 97%